2019
DOI: 10.1016/j.archoralbio.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced basal autophagy supports ameloblastoma-derived cell survival and reactivation

Abstract: Objectives: Ameloblastoma is an aggressive odontogenic jaw neoplasm. Its unlimited growth confers high potential for malignant transformation and recurrence. It is unclear why ameloblastoma is highly recurrent despite surgical resection with a wide margin of normal tissue. While canonical autophagy can be used to degrade and eliminate damaged cellular components, it is also a protective mechanism that provides energy and vital metabolites for cell survival. We used ameloblastoma-derived cells to test the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Accumulating evidence suggests that lncRNA as a ceRNA regulates OA progression by sponging miRNAs [ 43 , 44 ]. Previously, low HOTAIRM1-1 expression was found to inhibit MSC viability and differentiation via the miR-125b/BMPR2 axis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that lncRNA as a ceRNA regulates OA progression by sponging miRNAs [ 43 , 44 ]. Previously, low HOTAIRM1-1 expression was found to inhibit MSC viability and differentiation via the miR-125b/BMPR2 axis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that epithelial cells of AB have stronger autophagy activity than mesenchymal cells, human odontogenic cells, and maxillary mesenchymal stem cells, indicating that autophagy may promote the cell viability of residual AB epithelial cells in the hypoxic tumor microenvironment that is in relation to local invasion of AB ( 7 ). Consistently, our data showed that inhibiting autophagy significantly weakened cell proliferation of AM-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of tumor development, autophagy may restrain the progression of tumors, but once the tumor is formed, autophagy may facilitate survival and growth of tumor cells (6). A previous study has found that LC-3 and p62 were highly expressed in primary AB-derived epithelial cells (7). Therefore, research on autophagy in odontogenic tumors is of great significance for understanding tumor occurrence and development.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagic mechanisms may play a role in the behavior of ameloblastomas [6]. Autophagy is a well-coordinated process involving the sequestration of damaged proteins in double-membraned vesicles known as autophagosomes [18].…”
Section: Discussionmentioning
confidence: 99%
“…One study attributed the local invasiveness of ameloblastoma to expression of proteins inducing invadopodia [5]. More recently, Sharp et al inferred that the progression and invasive potential of an ameloblastoma could be associated with the autophagy process [6]. Autophagy is a catabolic process whereby autophagic vesicles sequester injured organelles and proteins for degradation through fusion with the lysosomes [7].…”
Section: Introductionmentioning
confidence: 99%